ASSESSMENT SOME OF THE GEOTECHNICAL PROPERTIES OF MUNICIPAL SOLID WASTE AT SORAN WASTE DUMPING SITE, KURDISTAN REGION OF IRAQ - Sofi, TAWREZ SHAABAN; KAKRASUL , JAMAL ISMAEL; QURTAS , SHERWAN SHARIF (Journal of Duhok University, 2023)
The majority of waste disposal (landfill) sites are made up of the municipal solid waste (MSW), that requires a proper management and engineering design of the landfill sites is must; otherwise they hurt the environment. The geotechnical properties of MSW are essential factors in the overall stability of landfills. The aim of this research is to assess the strength properties of MSW from a main dumping site in Soran city, Kurdistan region of Iraq. For this purpose, seven Shelby tube samples of MSW were collected at the different locations and depths of the dumpsite. Natural moisture content (NMC) and unconfined compressive strength (UCS) tests were performed on the collected samples. Results revealed that the MSW samples collected in the middle of the dumpsite had higher NMC and lower UCS than the samples collected at the edge sides of the dumpsite due to higher waste quantity in the middle of the dumpsite. Hence, the strength properties of MSW decreased with increasing waste quantity. In addition, the NMC and UCS of the MSW samples increased with increasing depth. Eventually, the unconfined compression results verified the stability of the landfill.